Pengelolaan ekosistem mangrove untuk ruang terbuka hijau sebagai mitigasi gas rumah kaca di kawasan Sungai Tallo Kota Makassar - Rahman Rahman; Hefni Effendi; Iman Rusmana; Fredinan Yulianda; Yusli Wardiatno (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
One of the ecological functions of mangroves ecosystem is to store carbon. Yet, on the other hand it also has the potential to cause greenhouse gas emissions through litter degradation even though its value is lower compared to the absorption value. Based on these two facts, mangrove management as a Green Open Space in the Tallo river area of ​​Makassar City needs to consider involving the participation of the community and the government as stakeholders. The research was conducted by desk work, literature study and respondent interviews regarding perceptions and participation in mangrove management. The results showed that the total uptake of mangrove carbon in the Tallo river in Makassar city was 351.02 tons CO2/ha, oxygen supply 255.29 O2-equivalent/ha, and the potential for global warming was 252.41 mg/ m2/hour consisting of 194, 33 mg/m2/hour of CO2 gas, 15.76 mg/m2/hour of CH4 gas, and 42.33 mg/m2/hour of N2O gas. The results of community perception and participation analysis show that around 89% of the community strongly agreed and supported the government in the effort to manage mangroves as a green open space. Based on this, the ecosystem in the Tallo river is very suitable to be managed for green open space as fresh air supplier and CO2 adsorber as well as a noise reduction from vehicle or industrial engines in Makassar city.